2010
DOI: 10.1016/j.freeradbiomed.2010.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Hydroethidine- and MitoSOX-derived red fluorescence is not a reliable indicator of intracellular superoxide formation: Another inconvenient truth

Abstract: Hydroethidine (or dihydroethidium) (HE) is the most popular fluorogenic probe used for detecting intracellular superoxide radical anion. The reaction between superoxide and HE generates a highly specific red fluorescent product, 2-hydroxyethidium (2-OH-E+). In biological systems, another red fluorescent product, ethidium (E+), is also formed, usually at a much higher concentration than 2-OH-E+. In this article, we have reviewed the methods to selectively detect the superoxide-specific product (2-OH-E+) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
399
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 447 publications
(430 citation statements)
references
References 354 publications
15
399
2
3
Order By: Relevance
“…We have previously shown that the fluorescence spectral overlap between 2-OH-E ϩ and E ϩ makes it impossible to assign HE-derived red fluorescence to either 2-OH-E ϩ or E ϩ without guidance from HPLC measurements (22). As shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have previously shown that the fluorescence spectral overlap between 2-OH-E ϩ and E ϩ makes it impossible to assign HE-derived red fluorescence to either 2-OH-E ϩ or E ϩ without guidance from HPLC measurements (22). As shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Under these conditions, it is likely that there is negligible formation of ONOO Ϫ or HOCl. The global profiling of HE and HE-derived oxidation products is essential for proper interpretation of results obtained under different experimental conditions (22). Measurement of intracellular superoxide via monitoring of 2-OH-E ϩ , the diagnostic marker product of O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrimination between these two is still be possible, however, due to an extra excitation band between 350 and 400 nm for 2-OH-E + (Robinson et al 2006). However, as the ratio E + /2-OH-E + is often 10 or more, contribution of E + might still be significant (Zielonka and Kalyanaraman 2010). MitoSOX is a DHE derivative coupled to a positively charged triphenylphosphonium group (TPP + ), enabling efficient targeting to the mitochondria for selective detection of mitochondrial O 2…”
Section: Sensorsmentioning
confidence: 99%
“…525 nm, em. 616 nm) and is often present at a much higher concentration (Zielonka and Kalyanaraman 2010). Discrimination between these two is still be possible, however, due to an extra excitation band between 350 and 400 nm for 2-OH-E + (Robinson et al 2006).…”
mentioning
confidence: 99%